2020
DOI: 10.1101/2020.03.26.010181
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A regulatory program for initiation of Wnt signaling during posterior regeneration

Abstract: 11Whole-body regeneration requires the re-establishment of body axes for appropriate patterning 12 of new and old tissue. Wnt signaling has been utilized to correctly regenerate tissues along the 13 primary axis in many animals. However, the causal molecular mechanisms that first launch Wnt 14 signaling during regeneration are poorly characterized. We used the acoel worm Hofstenia 15 miamia to identify processes that initiate Wnt signaling. Transcriptome profiling, in situ 16 hybridization, and functional stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The function of muscle cells in regeneration has recently been emphasized in planarians (Witchley et al, 2013;Scimone, Cote and Reddien, 2017;Tewari et al, 2019;Scimone et al, 2020), where they appear to guide progenitor cells to their correct location, notably by establishing a chemical coordinate system, through release of signaling molecules (Position Control Genes, PCGs; e.g., several wnt, fz-4, bmp4, admp). Quite remarkably, despite the ancient divergence of acoels and planarians (550 mya), Hofstenia body wall muscles seem to share, at least partially, this instructive role as they express homologs of PCGs that are required for patterning of tissue during regeneration, and, as in planarians, PCG expression is triggered in muscle by regeneration (Raz et al, 2017;Ramirez, Loubet-Senear and Srivastava, 2020). Our results show a high degree of interconnection between the different muscle compartments (Fig.…”
Section: High Resolution Description Of the Musculaturementioning
confidence: 60%
See 1 more Smart Citation
“…The function of muscle cells in regeneration has recently been emphasized in planarians (Witchley et al, 2013;Scimone, Cote and Reddien, 2017;Tewari et al, 2019;Scimone et al, 2020), where they appear to guide progenitor cells to their correct location, notably by establishing a chemical coordinate system, through release of signaling molecules (Position Control Genes, PCGs; e.g., several wnt, fz-4, bmp4, admp). Quite remarkably, despite the ancient divergence of acoels and planarians (550 mya), Hofstenia body wall muscles seem to share, at least partially, this instructive role as they express homologs of PCGs that are required for patterning of tissue during regeneration, and, as in planarians, PCG expression is triggered in muscle by regeneration (Raz et al, 2017;Ramirez, Loubet-Senear and Srivastava, 2020). Our results show a high degree of interconnection between the different muscle compartments (Fig.…”
Section: High Resolution Description Of the Musculaturementioning
confidence: 60%
“…Hofstenia is capable of this "wholebody" regeneration and harbors adult stem cells referred to as "neoblasts". A sequenced genome, transcriptomic resources, and robust and systemic RNA interference (RNAi) have enabled functional studies of regeneration and stem cells in Hofstenia (Srivastava et al, 2014;Raz et al, 2017;Gehrke et al, 2019;Ramirez, Loubet-Senear and Srivastava, 2020), and we sought to leverage the biology of this system further by developing tools for transgenesis.…”
Section: Introductionmentioning
confidence: 99%
“…During Hydra head regeneration, an enhancer collection become accessible allowing the expression of cWNT genes in head organizing cells (69,70). In acoels, egr is expressed after amputation triggering the expression of wnt3, which participates in the posterior specification (67,71). As recently proposed, it could be that enhancers may be maintained as part of conserved gene regulatory network modules over evolution (72).…”
Section: Establishment Of the Posterior Organizer Requires A Foxg Medmentioning
confidence: 94%
“…Genomic studies in different regenerative species have identified different sets of TFs as regulators of cWNT genes during regeneration. In Drosophila, injured imaginal disc required 'regenerative enhancers' to trigger wingless expression and the regeneration process (66)(67)(68). During Hydra head regeneration, an enhancer collection become accessible allowing the expression of cWNT genes in head organizing cells (69,70).…”
Section: Establishment Of the Posterior Organizer Requires A Foxg Medmentioning
confidence: 99%
“…A conserved role for bZIPs in activating Wnt signaling during regeneration is supported by the findings that Erk is required for the injury-induced activation of Wnt signaling in planarians (Owlarn et al, 2017) and bZIP TFBMs are required for Wnt expression during imaginal wing disc regeneration in Drosophila (Harris et al, 2016). In contrast, it was recently reported that the zinc finger TF Egr is required for Wnt expression during acoel regeneration (Ramirez et al, 2020). It will therefore be important for future research to characterize injury-responsive GRNs across diverse animal taxa to better understand the evolutionary history of Wnt signaling and its regulation during wound repair.…”
Section: Discussionmentioning
confidence: 95%